Effective Use of LMS in Inculcating 21st Century Skills among University Graduates - A Conceptual Success Model - Ramli R.; Yahya H. (Institute of Electrical and Electronics Engineers Inc., 2023)
Education computing; Electronic assessment; Learning systems; Students; Teaching; Blended learning; Industrial revolutions; Learning management system; Multimedia elements; Skills development; Teaching and learning; Tertiary education; University graduates; Engineering education